Rada jako narzędzie perswazji w projekcie dydaktycznym O wychowaniu dzieci uchodźców Juliusza Jedlińskiego - Pałucka-Czerniak, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article presents the use of a simple genre of advice in a teaching project from the nineteenth century. The publication which is the subject of the analysis is by Julius Jedliński, and refers to the Polish national school called L’École polonaise des Batignolles in Paris. This document certifies that emigres discussed the value of the Polish language as a determinant of Polish identity. Effective ways of teaching the children of immigrants Polish language and culture were sought. The author of the publication presented the concept of changes in the school curriculum. As a means of persuasion he primarily used advice. The reception of the proposal by Jedliński was not favourable. The analysis of responses reveals transformations in the basic block of communicative intentions of the advice, which is interpreted as an order, complaint, or even a threat. On this basis, the attention is drawn to the importance of the communicative context in the interpretation of advice. As a result of the public nature of an act of speech and the extension of the audience while maintaining the desired recipient, the decisiveness of any advice is increased and a modification of a simple genre takes place.